International Students’ Suggestions for What Universities Can Do to Better Support Their Mental Wellbeing - Marangell, Samantha; Baik, Chi (Journal of International Students, 2022)
This article aims to expand understanding of how to support international students’ mental wellbeing in Australian higher education. It presents findings from a study which explored international students’ own suggestions for how universities could improve their wellbeing. Qualitative responses were analyzed from 601 international students at one large, metropolitan university in Australia. Findings emphasize the relationship between course experience and student wellbeing and suggest that universities could improve international students’ wellbeing by focusing on improving their learning experiences and fostering a sense of belonging.